Ativação do subtipo de receptor 5-HT1A do núcleo paraventricular do hipotálamo sobre a ingestão de água e sódio - Villa, Patrícia de Souza (2006)
Hypothalamic paraventricular nucleus (PVN) has an important role in the hydroeletrolytic balance and it also participates in the regulation of water and sodium intake. Recent researches described the presence of 5-HT1 receptors in the central nervous system, standing out the subtypes 5-HT1A, 5-HT1B, 5-HT1C and 5-HT1D. The receptor 5-HT1A was one of the firsts to be identified and it is found in the somatodendritic and pos-synaptic forms. It has been showed the participation of PVN 5-HT1A receptor in the hydroeletrolytic balance. Therefore, the aim of this study was: a) To investigate the effects of bilateral injections of serotonin (5-HT) in the PVN about water intake induced by water deprivation and water and 1.8% NaCl intake induced by sodium depletion; b) To investigate the effects of 8-OH-DPAT injection, an 5-HT1A agonist, in the PVN about water intake induced by water deprivation and water and 1.8% NaCl intake induced by sodium depletion; c) To investigate the action of pMPPF, an 5-HT1A antagonist, into the PVN on the effects of 5-HT and 8-OH-DPAT on the water and 1.8% NaCl intake. Holtzman rats (280-320 g) were submitted to the implant of cannulas bilaterally in the PVN. For the implant, the animals were adapted to a stereotaxic apparatus. Using the bregma, introduction points of the stainless steel cannulas were identified according to the coordinates: 1.8 mm caudal to bregma, 0.6 mm lateral to the midline and 5.0 mm below dura mater. 5-HT injections (10, 20, 40 and 50 µg/ 0,2 µl) in the PVN reduced the water intake (13.4±2.0; 12.6±1.3; 12.9±1.0 and 9.0±2.9 ml/ 30 min vs. sal: 18.4±0.8 ml/ 30 min, respectively, n = 6-8) and the doses 10 and 20 µg/ 0.2 µl reduced the 1.8% NaCl intake (7.9 ± 3.0 and 9.0 ± 2.1 ml/ 30 min, respectively, vs. sal: 17.7 ± 1.8 ml/ 30 min, n = 7). 8-OH-DPAT injections (1.0, 2.5 and 5.0 µg/ 0.2 µl) in the PVN reduced the water intake (15.4 ± 1.3; 14.8 ± 1.2 and 14.2 ± 0.9 ml/ 120 min vs. sal: 19.1 ± 1.0 ml/ 120 min, n = 10) and the doses 2.5 µg and 5 µg also reduced 1.8% NaCl intake (12.4 ± 2.7 ml/ 60 min vs. sal: 19.3 ± 1.0 ml/ 60 min; 12.2 ± 1.8 ml/ 120 min vs. sal: 20.0 ± 1.0 ml/ 120 min, respectively, n = 9). pMPPF bilateral injections (5-HT1A antagonist) preview to 8-OH-DPAT injections have completely blocked the inhibitory effect over water intake (sal + DPAT: 13.8 ± 1.1 ml/ 90 min vs. pMPPF + DPAT: 16.4 ± 1.1 ml/ 90 min, n = 12) and 1.8% NaCl (sal + DPAT: 11.4 ± 2.9 ml/ 30 min vs. pMPPF + DPAT: 17.6 ± 1.7 ml/ 30 min, n = 8). 5-HT1A antagonist partially reduced the inhibitory effect of 5-HT on water intake induced by water deprivation (sal+5-HT: 5.9±1.6 ml/ 30 min vs. pMPPF+5-HT: 12.3±1.1 ml/ 30 min, n=12) as well as on sodium intake induced by sodium depletion (sal+5-HT: 2.8±1.3 ml/ 30 min vs. pMPPF+5-HT: 12.3±1.9 ml/ 30 min, n=15). Our results demonstrate the presence of serotonergic mechanisms in PVN inhibiting water and sodium intake and also the participation of pos-synaptic 5-HT1A receptors on water intake control induced by water deprivation and on sodium intake induced by sodium depletion, and that this receptor doesn t have a tonic inhibitory effect. This work also showed others subtypes serotonergic PVN receptors participating in the dipsogenesis and natriorexigenesis control.